Countering the Waves: Vietnam’s Bilateral Relations with the Philippines, Malaysia, and Indonesia in the South China Sea - Co Huynh Thien Kim (Jurnal Impresi Indonesia, 2025)
China’s increasing assertiveness in the South China Sea has intensified security pressures on Vietnam. However, existing studies have not fully explained why Vietnam prioritizes bilateral cooperation with the Philippines, Malaysia, and Indonesia. This article addresses this gap by examining Vietnam’s alignment choices from 2016 to 2024 through Stephen Walt’s Balance of Threat theory. Using a qualitative within-case design, the study operationalizes Walt’s four variables - aggregate power, geographic proximity, offensive capabilities, and perceived intentions - to analyze how Vietnam interprets China’s behavior and why these perceptions push Hanoi to strengthen ties with the three Southeast Asian partners. The findings show that China is the only actor that fulfills all four components of a perceived threat, while the Philippines, Malaysia, and Indonesia are viewed as non-threatening states with shared interests in upholding maritime rights under the UNCLOS. As a result, Vietnam expanded defense exchanges, coast guard cooperation, and diplomatic coordination with these partners to mitigate China’s strategic advantages. This article contributes to existing scholarship by providing a structured, theory-based explanation of Vietnam’s selective mini-lateral cooperation, which is an underdeveloped aspect in existing scholarship.